Peran Semangat Kerja Memediasi Pengaruh Lingkungan Kerja terhadap Produktivitas Kerja Karyawan Non Medis RSUD Sanjiwani Gianyar - Lastiari, Ni Kadek Wulan; Kawiana, I Putu; Ary Pratiwi, Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the mediating role of work morale and the influence of the work environment on the work productivity of non-medical employees at Sanjiwani Hospital, Gianyar. The sample for this research was all 62 contract non-medical employees at Sanjiwani Hospital, Gianyar. Data were collected by distributing questionnaires using a Likert scale with a score of 1 to 5. The data analysis technique used path analysis. The research results show: (1) The work environment has a positive and significant effect on work morale at Sanjiwani Hospital, Gianyar. (2) The work environment has a positive and significant effect on work productivity at Sanjiwani Hospital, Gianyar. (3) Work enthusiasm has a positive and significant effect on work productivity at Sanjiwani Hospital, Gianyar. (4) Work enthusiasm plays a mediating role in the influence of the work environment on work productivity at Sanjiwani Hospital, Gianyar.